Analysis of the effects of dimples on the performance of Small-Scale Horizontal Axis Wind Turbines with CFD - Muzaki, Imam; Ismail, Ismail (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2025)
The addition of dimples to small-scale wind turbine blades can improve the energy extraction of horizontal axis wind turbines (HAWTs). However, although there is some understanding of how dimples affect wind turbine power, the effects of specific wind turbine blade stress parameters remain to be investigated. This article describes the impact of adding dimples to small-scale horizontal axis wind turbine (SSHAWT) blades. The results showed that the addition of dimples to SSHAWT 3, revealed that the addition of dimples with 27 dimples resulted in the highest turbine power, compared to the baseline wind turbine blade, with an average turbine output power of 362.25 w, at a wind speed of 6 m/s. The addition of dimples to wind turbine blades can be a suggestion for improving the performance of small-scale wind turbines.